“Pillaring Effects” in Cross-Linked Cellulose Biopolymers: A Study of Structure and Properties - Inimfon A. Udoetok; Lee D. Wilson; John V. Headley (International Journal of Polymer Science)
Modified cellulose materials (CLE-4, CLE-1, and CLE-0.5) were prepared by cross-linking with epichlorohydrin (EP), where the products display variable structure, morphology, and thermal stability. Adsorptive probes such as nitrogen gas and phenolic dyes in aqueous solution reveal that cross-linked cellulose has greater accessible surface area (SA) than native cellulose. The results also reveal that the SA of cross-linked cellulose increased with greater EP content, except for CLE-0.5. The attenuation of SA for CLE-0.5 may relate to surface grafting onto cellulose beyond the stoichiometric cellulose and EP ratio since ca. 30% of the hydroxyl groups of cellulose are accessible for cross-linking reaction due to its tertiary fibril nature. Scanning electron microscopy (SEM) results reveal the variable surface roughness and fibre domains of cellulose due to cross-linking. X-ray diffraction (XRD) and 13C NMR spectroscopy indicate that cellulose adopts a one-chain triclinic unit cell structure (P1 space group) with gauche-trans (gt) and trans-gauche (tg) conformations of the glucosyl linkages and hydroxymethyl groups. The structural characterization results reveal that cross-linking of cellulose occurs at the amorphous domains. By contrast, the crystalline domains are preserved according to similar features in the XRD, FTIR, and 13C NMR spectra of cellulose and its cross-linked forms. This study contributes to an improved understanding of the role of cross-linking of native cellulose in its structure and functional properties. Cross-linked cellulose has variable surface functionality, structure, and textural properties that contribute significantly to their unique physicochemical properties over its native form.